How Ritual an Animal?: Harvey Whitehouse on Ritual, Trust, and Cooperation - Sterelny, Kim (Journal for the cognitive science of religion, 2020)
Harvey Whitehouse documents the great variety of ritual in human life, while offering a unified framework. Ritual’s essential social role is to support social cohesion and cooperation, but it does so via distinct mechanisms: through social fusion and through social identification. For, despite variation, ritual clusters at two poles: rare, intense, often aversive rituals; and frequent, low arousal rituals. Those frequent rituals operate through social identification primed by mutual recognition of common doctrine. In principle, this mechanism is scale independent. Rare, intense rituals generate cohesion through social fusion, itself triggered by shared, congruent autobiographical memory. This is intrinsically a small-scale mechanism. In this paper, I (i) argue that cost-based analyses of the function of ritual have a larger scope than Whitehouse supposes, (ii) offer a modified view of social fusion and the role of autobiographical memory, and (iii) argue that the primary upshot of doctrinal ritual is the legitimation of hierarchy rather than social cohesion over large social scales.